Telecommuting potential analysis - Babu, D.; Ramalho, N.; Falcão, P. F. (Global Business and Economics Review, 2020)
Commuting is a problem for developed societies that translates into economic, social and environmental losses. This study is set to explore the potential of telecommuting. The empirical study started with interviews to build a survey that was answered by 126 Lisbon commuters. Results show interviewees perceived telecommuting consequences are in line with extant research and that attitudes towards telecommuting (productivity, and cost savings) are predictors of the intention to accept telecommuting offers. Likewise, professional tenure and work-to-home stress foster a more favourable attitude related to productivity / quality of working life while displacement mode (active) and home-to-work stress foster a more favourable attitude related with cost savings. The study concludes that there is considerable potential for telecommuting and that the process of implementing telecommuting as an HRM policy is doable based on the attitudes identified in the model developed.